Effect of zink oxyde nanoparticles on the test function of water organisms of different trophic levels. Issue 1 (October 2015) - Morgalev, Yu; Morgaleva, T; Gosteva, I; Morgalev, S; Kulizhskiy, S; Astafurova, T
Abstract: The toxicity of zinc oxide nanoparticles (nZnO) with particle size Δ50 = 20 nm was evaluated according to the degree of toxicity of the aqueous disperse system (DS) with biological testing methods using a set of test organisms representing the major trophic levels.We observed the influence of the concentration degree of nZnO on toxic effects level on the fluorescence of the bacterial biosensor "Ekolyum-13", the chemotactic response of ciliates Paramecium caudatum, the rate of growth of unicellular algae Chlorella vulgaris Bayer, mortality of entomostracans Daphnia magna Straus and fish Danio rerio . The detected values of L(E)C50 are: for biosensor "Ekolyum-13" – 0.30 mg/L, for ciliates Paramecium caudatum – 0.14 mg/L, for Chlorella vulgaris Bayer – 0.17 mg/L and for Daphnia magna Straus – 0.52 mg/L. No toxicity of nZnO was detected in relation to fish Danio rerio, L(E)C50 > 100 mg/L. In assessing the maximum effect of nZnO according to GHS and EU Directive 93/67/ EEC, it is assigned to dangerous substances with a high degree of toxicity "Acute toxicity 1".